1982
DOI: 10.1002/pssa.2210720216
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Observations of Copper Vacancy Ordering in Chalcocite (Cu2S) and the Transformation to Djurleite (Cu1.97 to 1.94S)

Abstract: The technique of high resolution transmission electron microscopy (TEM) permits the first real space observations of the ordering of copper in the sulfur sublattices of chalcocite (Cu2S) and djurleite (Cu1.97 to 1.94S). Copper sulfide thin films formed by the ion exchange process in CdS single crystals are shown to be composed of small domains of the two phases (≈ 10 to 100 nm in diameter), separated by abrupt coherent interfaces. Strain calculations for these interfaces agree qualitatively with experimental o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 10 publications
0
43
0
Order By: Relevance
“…An interesting control parameter for the functionality of the copper sulfide nanocrystals is by stoichiometric tuning . Due to the low chemical potential of Cu in these systems, they show tendency towards stoichiometric diversity through the process of Cu vacancy creation, as reported in binary, ternary and quaternary metal chalcogenides and chalcopyrites . Furthermore, in nanomaterials, where surface effects are dominant, vacancy formation may be enhanced in comparison to the bulk materials, especially in processes involving small atoms diffusion to the interfaces.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…An interesting control parameter for the functionality of the copper sulfide nanocrystals is by stoichiometric tuning . Due to the low chemical potential of Cu in these systems, they show tendency towards stoichiometric diversity through the process of Cu vacancy creation, as reported in binary, ternary and quaternary metal chalcogenides and chalcopyrites . Furthermore, in nanomaterials, where surface effects are dominant, vacancy formation may be enhanced in comparison to the bulk materials, especially in processes involving small atoms diffusion to the interfaces.…”
Section: Figurementioning
confidence: 99%
“…The peak‐voltage down‐shift may be attributed to p ‐type doping in the oxidized Cu 2− x S nanocrystals, which takes place during oxidation of the copper(1+) ions . Accordingly, the decrease in potential required for copper‐ion oxidation may be assigned to a formation of an in‐gap state close to the valance band (VB) (see Scheme in Figure e).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…12,13,16,21 Luther et al, 12 Kriegel et al, 16 and Hsu et al 21 have reported tunability of the LSPR frequency in Cu 2−x S nanocrystals through exposure to air, which introduces copper vacancies. 16,22 Other methods to control the LSPR frequency in semiconductor nanocrystals focus on synthetic routes or chemical treatments to selectively modify the geometry and size of the LSPR-supporting phase. Targeted phosphorus doping of Si nanowires has been shown to produce segmented nanowires consisting of alternating insulating and conducting regions.…”
Section: Introductionmentioning
confidence: 99%